Role of smart tourism technology in heritage tourism development - Yogesh Dwivedi (Journal of Sustainable Tourism, 2023)
This study investigates the role of smart tourism technology (STT) attributes (accessibility, informativeness, interactivity, and personalisation) in creating a positive STT experience, influencing tourists’ intentions to revisit, thus benefiting the image of a heritage site. A conceptual model was developed by formulating key reasoning from the elaboration likelihood model (ELM) and flow theory. Four hundred samples were collected from four national heritage sites in India to test the model. The results indicated that the STT role is critical in developing tourists’ STT experience and revisit intention, with STT attributes representing the central route of elaboration tending to play a stronger role. This study discusses results across age (old/young) and gender (male/female) with theoretical implications that could also contribute meaningful insights to marketers, government bodies, and corporations involved in tourism development. Importantly, the emergence of STT and the dimensions of the heritage site image are discussed from a sustainability perspective.